Travessia poética: o pacto entre crítica e escuta em "Grande Sertão Veredas" - CARVALHO, Taís Salbé (Universidade Federal do Pará, 2017)
The research proposes an exercise in literary criticism that focuses on the dialogical pact between critique and listening, in Grande Sertão: Veredas, novel by Guimarães Rosa, published in 1956, from a deconstruction of the metaphysical tradition, which thinks that art as mere representation of reality, and no longer as a staging of issues of the real. Therefore, we dialogue with a type of hermeneutics that questions the concepts of representative criticism that, in our view, imprison the literary work, since it analyzes it from predetermined theories, and we give ourselves to the exercise of criticism as listening originating from the questions put into work by the literary work. In this exercise we are called to think the unthought of thought, letting the work itself claim its theory, summoning us to critical listening. In order to do so, it was necessary to question the original questions manifested in Rosa's novel, such as: Language, Art, Truth (unveiling), Being, Being-in-the-World, Crossing, Dialogue and Pact with the Devil. In this sense, the essential relation between art and truth, in which this is the very dynamic of veiling-unveiling-veiling of the being of things, of physis. The work of art is nothing more than this dynamic and in them and through them we seek to traverse our poetic crossing, questioning us from the questions that are manifesting, and of which we are also bestowal, in search of our poetic learning.